2018
DOI: 10.4218/etrij.2017-0084
|View full text |Cite
|
Sign up to set email alerts
|

SDN-Based Hierarchical Agglomerative Clustering Algorithm for Interference Mitigation in Ultra-Dense Small Cell Networks

Abstract: Ultra‐dense small cell networks (UD‐SCNs) have been identified as a promising scheme for next‐generation wireless networks capable of meeting the ever‐increasing demand for higher transmission rates and better quality of service. However, UD‐SCNs will inevitably suffer from severe interference among the small cell base stations, which will lower their spectral efficiency. In this paper, we propose a software‐defined networking (SDN)‐based hierarchical agglomerative clustering (SDN‐HAC) framework, which leverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, interferencecentric sufferings of UD-SCNs are highly imperative. In [127], the authors suggested centralized control of subchannels called SDN-HAC (SDN-based Hierarchical Agglomerative Clustering). SDN-HAC decides cluster merging on suitability function-based similarity criterion.…”
Section: K Hierarchical Agglomerative Clusteringmentioning
confidence: 99%
“…Therefore, interferencecentric sufferings of UD-SCNs are highly imperative. In [127], the authors suggested centralized control of subchannels called SDN-HAC (SDN-based Hierarchical Agglomerative Clustering). SDN-HAC decides cluster merging on suitability function-based similarity criterion.…”
Section: K Hierarchical Agglomerative Clusteringmentioning
confidence: 99%
“…In [465], the optimal number of reserved channels is decided based on secondary user retainability and channel availability, while an application policy considers the primary user channel availability minimum by monitoring the incoming traffic requests. A Hierarchical Agglomerative Clustering (HAC) framework to control all sub-channels in the network to decide on cluster merging in ultra-dense small cell networks with an application policy to mitigate severe interference among small cell base stations has been proposed in [466]. Furthermore, mobility management also includes offloading, such as Wi-Fi device to device offloading from cellular networks when device to device communication is available [467].…”
Section: Network Managementmentioning
confidence: 99%
“…Following considerable research efforts, many schemes have been proposed to minimize the effect of co-tier interference in HetNets, including clustering techniques, cognitive approaches, resource allocation solutions and power control techniques [7][8] [9] [10]. Among them, Sultan et al [11] discussed power and radio resource management techniques to mitigate the co-tier interference in femtocells.…”
Section: Introductionmentioning
confidence: 99%